2022
DOI: 10.1096/fasebj.2022.36.s1.r3702
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of glutamate transporters as a potential therapeutic intervention for neurological disorders

Abstract: Excitatory amino acid transporters (EAATs) are key proteins in the CNS that regulate glutamate levels and, therefore, control excitatory neurotransmission and limit excitotoxicity. EAATs are trimers, with each protomer consisting of a scaffold domain, and a transport domain that slides along the scaffold domain in an “elevator‐like motion” to move synaptic glutamate into astrocytes and neurons. Our lab has discovered novel positive allosteric modulators (PAMs) of EAAT2, the main EAAT subtype responsible for gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Glutamate is a major excitatory neurotransmitter that acts at various excitatory synapses in the nervous system. Studies have confirmed that high concentrations of glutamate can induce neuronal damage and apoptosis [96]. The glutamate-induced Ca 2+ overload hypothesis has been widely accepted as the mechanism of neuronal injury in glutamate-induced excitotoxicity [97].…”
Section: Discussionmentioning
confidence: 98%
“…Glutamate is a major excitatory neurotransmitter that acts at various excitatory synapses in the nervous system. Studies have confirmed that high concentrations of glutamate can induce neuronal damage and apoptosis [96]. The glutamate-induced Ca 2+ overload hypothesis has been widely accepted as the mechanism of neuronal injury in glutamate-induced excitotoxicity [97].…”
Section: Discussionmentioning
confidence: 98%